2022
DOI: 10.1017/jfm.2022.897
|View full text |Cite
|
Sign up to set email alerts
|

Reorganisation of turbulence by large and spanwise-varying riblets

Abstract: We study the flow above non-optimal riblets, specifically large drag-increasing and two-scale trapezoidal riblets. In order to reach large Reynolds numbers and large scale separation while retaining access to flow details, we employ a combination of boundary-layer hot-wire measurements and direct numerical simulation (DNS) in minimal-span channels. Although the outer Reynolds numbers differ, we observe fair agreement between experiments and DNS at matched viscous–friction-scaled riblet spacings $… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 77 publications
(212 reference statements)
3
16
0
Order By: Relevance
“…Moreover, for studies with δ + ≈ 1000-10 000 and h/δ 1, a decrease in κ is still observed with an increase in Reynolds number for the same roughness, suggesting an in-depth modification of the flow by the substrates (Suga et al 2010;Manes et al 2011;Fang et al 2018;Okazaki et al 2021Okazaki et al , 2022. Some studies have observed that permeable roughness could lead to an approximately 50 % drop in κ, which is more substantial than that induced by the impermeable roughness with the same geometry, implying that permeability may enhance the extent and intensity of roughness effects (Okazaki et al 2021(Okazaki et al , 2022Esteban et al 2022;Karra et al 2022). Nevertheless, the prediction of u τ , which is of great importance for the assessment of outer-layer similarity, remains a challenge in experiments (Chung et al 2021).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, for studies with δ + ≈ 1000-10 000 and h/δ 1, a decrease in κ is still observed with an increase in Reynolds number for the same roughness, suggesting an in-depth modification of the flow by the substrates (Suga et al 2010;Manes et al 2011;Fang et al 2018;Okazaki et al 2021Okazaki et al , 2022. Some studies have observed that permeable roughness could lead to an approximately 50 % drop in κ, which is more substantial than that induced by the impermeable roughness with the same geometry, implying that permeability may enhance the extent and intensity of roughness effects (Okazaki et al 2021(Okazaki et al , 2022Esteban et al 2022;Karra et al 2022). Nevertheless, the prediction of u τ , which is of great importance for the assessment of outer-layer similarity, remains a challenge in experiments (Chung et al 2021).…”
Section: Introductionmentioning
confidence: 93%
“…where k s is the equivalent sand grain roughness height) and Kármán constant (κ). The abbreviations for the studies are B06 (Breugem et al 2006), S10 (Suga et al 2010), M11 (Manes et al 2011), R17 (Rosti & Brandt 2017), K17 (Kuwata & Suga 2017), S20 (Shen, Yuan & Phanikumar 2020), K21 (Kazemifar et al 2021), K23 (Karra et al 2022), E22 (Endrikat et al 2022), F18 (Fang et al 2018, O21 (Okazaki et al 2021) and O22 (Okazaki et al 2022). Note that δ + denoted by * is estimated from k + s and k s /δ from S10.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the application, saving both energy and time could be important. Frohnapfel et al (2012) propose that operation of a drag-reducing mechanism with matched power input (τ w U b = const.) leads to simultaneous saving of pumping energy (due to the reduction in τ w ) and time (due to the increase in U b ).…”
Section: Simulation Casesmentioning
confidence: 99%
“…Techniques for flow control cover a variety of fields, and have been extensively reviewed (White & Mungal 2008;Dean & Bhushan 2010;Luchini & Quadrio 2022). Flow control devices are usually divided into two groups: passive devices that are fixed in place and do not change their shape or function in time, such as vortex generators (Lin 2002;Koike, Nagayoshi & Hamamoto 2004;Aider, Beaudoin & Wesfreid 2010) and riblets (García-Mayoral & Jiménez 2011Endrikat et al 2021a,b;Modesti et al 2021;Endrikat et al 2022;Rouhi et al 2022), and active devices that can be actuated in some way, such as targeted blowing (Abbassi et al 2017) or intermittent blowing and suction (Segawa et al 2007;Hasegawa & Kasagi 2011;Yamamoto, Hasegawa & Kasagi 2013;Schatzman et al 2014;Kametani et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation